2014
DOI: 10.2139/ssrn.2558932
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Policy for Inclusive Growth: An Overview

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…By attaining education, poor workers increase the income of their households. Government, thus, plays a very serious role by providing decent lives to poor by making expenditures on schooling, high professional education, hospitals and nursing homes (Estrada et al , 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…By attaining education, poor workers increase the income of their households. Government, thus, plays a very serious role by providing decent lives to poor by making expenditures on schooling, high professional education, hospitals and nursing homes (Estrada et al , 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Health expenditures narrow down the health gaps between rich and poor as poor people are less healthy than rich people because they do not have access to better health. Government can make contribution in providing equal health opportunities to all by spending on health-related facilities (Estrada et al , 2014). Warr (2003) also suggested that only pro-poor fiscal allocation can play a significant role in reducing poverty and inequality.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Untuk menerapkan cash conditional transfer (CCT) secara intensif di Asia, harus dilakukan secara hati-hati sebab pertumbuhan ekonomi di Asia relatif lebih cepat daripada Amerika Latin. Oleh karena itu, berdasarkan temuan Estrada et al (2014), pertumbuhan inklusif harus tetap memperhitungkan kondisi kesinambungan fiskal di negara Asia.…”
Section: Studi Terdahuluunclassified
“…'Growth is inclusive when it allows all members of a society to participate in and contribute to the growth process on an equal basis …' (Ali and Zhuang, 2007, p. 10). It focuses less on the benefits of growth particularly through tax-funded redistribution (Estrada et al, 2014), and more on the participation in economic processes. Ali and Zhuang's definition is also the one that the Asian Development Bank put forward in its Strategy 2020, and it applies this to various sectors, including human development and infrastructure.…”
Section: From Structural Adjustment and Growth-first To Equalities Anmentioning
confidence: 99%